Trace element concentrations in effluent of municipal wastewater treatment plants along the Turkish coasts and assessment of human health risk - Tolga Akdemir (Frontiers in Marine Science)
This study evaluated the concentrations, sources, and health risks of trace metals and metalloids in the effluents of 15 wastewater treatment plants (WWTPs) located along the Black Sea and the Sea of Marmara, ecologically and economically vital regions of Türkiye. Effluent samples were collected in winter and autumn, and metal concentrations were analyzed using ICP-MS to assess seasonal variations and potential risks. Results showed notable seasonal and regional differences, with aluminium (Al) and nickel (Ni) as the most abundant metals. The highest total metal concentration was recorded in autumn at station S2 (326.09 mg/L). Non-carcinogenic risks were negligible (HI< 1) across all stations, but low carcinogenic risks (10-6< CRi ≤ 10-4) for chromium (Cr) and nickel (Ni) were detected at some locations. Source apportionment using Principal Component Analysis revealed mixed geogenic and anthropogenic origins, primarily from industrial activities and urban runoff. While effluents generally complied with national standards, several metals exceeded international limits, highlighting risks to ecosystems and human health. These findings underscore the urgent need for stricter discharge regulations, improved treatment technologies, and continuous monitoring to mitigate the environmental and health impacts of WWTP discharges.